2020
DOI: 10.1186/s12865-020-00344-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed circulating exosomal lncRNAs in IgA nephropathy patients

Abstract: Background: Although immunoglobulin A nephropathy (IgAN) is one of the foremost primary glomerular disease, treatment of IgAN is still in infancy. Non-invasive biomarkers are urgently needed for IgAN diagnosis. We investigate the difference in expression profiles of exosomal long non-coding-RNAs (lncRNAs) in plasma from IgAN patients compared with their healthy first-degree relatives, which may reveal novel non-invasive IgAN biomarkers. Methods: We isolated exosomes from the plasma of both IgAN patients and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
(54 reference statements)
2
18
0
Order By: Relevance
“…Elderly individuals with the severity of coronary stenosis have elevated plasma miR-146a-5p levels [ 42 ]. Furthermore, Guo et al [ 43 ] reported a positive correlation between plasma miR-146a-5p and both carotid intima-media thickness and brachial-ankle pulse wave velocity in middle-aged to elderly diabetic patients. This discrepancy with our findings is most likely due to health status because the current study recruited only elderly individuals without a history of inflammatory and/or metabolic diseases, which may have eliminated some confounding factors compared with young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly individuals with the severity of coronary stenosis have elevated plasma miR-146a-5p levels [ 42 ]. Furthermore, Guo et al [ 43 ] reported a positive correlation between plasma miR-146a-5p and both carotid intima-media thickness and brachial-ankle pulse wave velocity in middle-aged to elderly diabetic patients. This discrepancy with our findings is most likely due to health status because the current study recruited only elderly individuals without a history of inflammatory and/or metabolic diseases, which may have eliminated some confounding factors compared with young adults.…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of exosomes has been recently investigated not only as less invasive biomarkers in a wide range of diseases, including various cancer (breast [Hannafon et al, 2016], cervix [Zheng et al, 2019], endometrium [Srivastava et al, 2018], gastric [Tang et al, 2020], lung [Cazzoli et al, 2013], pancreatic [Melo et al, 2015], prostate [Barceló et al, 2019], ovaries [Maeda et al, 2020]), Alzheimer's disease (Hamlett et al, 2017), Parkinson's disease (Kitamura et al, 2018), brain insulin resistance (Mullins et al, 2017), diabetes (Krishnan et al, 2019), cardiomyopathies (T. Wu, Chen, et al, 2018), nephropathies (Guo et al, 2020) and chronic kidney disease (Khurana et al, 2017), and multiple sclerosis (Ebrahimkhani et al, 2017), but also as therapeutic agents for both drug delivery vehicles (tumor therapy [Altanerova et al, 2019; Qi et al, 2016; Y. Tian et al, 2014], Parkinson's disease [Haney et al, 2015], cerebral ischemia therapy [T. Tian et al, 2018]) and a genetic or protein material transfer mediator (Alzheimer's disease [Yang et al, 2020], breast cancer [Sansone et al, 2017], ischemic myocardium [Gollmann‐Tepeköylü et al, 2020]) or graft‐versus‐host disease (Kordelas et al, 2014). In this regard, another potential translational perspective could be the transfusion or transferring of exosomes or enriched exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…diabetes (Krishnan et al, 2019), cardiomyopathies (T. Wu, Chen, et al, 2018), nephropathies (Guo et al, 2020) and chronic kidney disease (Khurana et al, 2017), and multiple sclerosis (Ebrahimkhani et al, 2017), but also as therapeutic agents for both drug delivery vehicles (tumor therapy [Altanerova et al, 2019;Qi et al, 2016;Y. Tian et al, 2014], Parkinson's disease [Haney et al, 2015], cerebral ischemia therapy [T. Tian et al, 2018]) and a genetic or protein material transfer mediator (Alzheimer's disease [Yang et al, 2020], breast cancer [Sansone et al, 2017], ischemic myocardium [Gollmann-Tepeköylü et al, 2020]) or graft-versus-host disease (Kordelas et al, 2014).…”
Section: Effects Of Exercise On Exosome Cargo (Proteins and Mirnas)mentioning
confidence: 99%
“…Guo et al used high-throughput RNA sequencing and qRT-PCR to test the exosomes isolated from plasma of IgAN patients and their healthy rst-degree relative. The results revealed that exsomal lncRNA-G21551 was down-regulated in IgAN patients, indicating its potential to serve as a non-invasive biomarker for IgAN [14]. In the study of Zuo et al, peripheral blood mononuclear cells were collected from both IgAN patients and healthy controls to identify differentially expressed lncRNAs and mRNAs by microarray analysis and quantitative polymerase chain reaction.…”
Section: Introductionmentioning
confidence: 99%